Learning Environment Management in the Arabic Language Camp Program for New Students of PBA IAIN Bone - Muh. Naufal Fitra; Muhammad Ibnu Tamam; Zakiyah Arifa; Nur Kholid; Farah Mardhiyyah Binti Ab Razak (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
Management of a conducive and supportive Arabic learning environment is a challenge for Arabic learning program managers. Therefore, the Student Association of the Arabic Language Education Department (HMPS PBA) IAIN Bone applied learning environment management through the implementation of the Arabic Language Camp program using an outdoor learning model specifically for new PBA IAIN Bone students. The implementation of the program was inseparable from the importance of implementing the actuating function in learning environment management. The purpose of this study is to provide an overview of the Arabic Language Camp program and the implementation of the actuating function in learning environment management in the Arabic Language Camp program in terms of leadership, motivation, and communication aspects. The approach used in this study is qualitative research with descriptive methods and uses in-depth interviews and documentation as data collection techniques. The informants are the directors, the committee, and the participants of this program. The results of this study showed that the Arabic Language Camp program was running well as planned. In addition, the implementation of the actuating function (leadership, motivation, and communication) in learning environment management is also going well. Therefore, participants felt that the managed learning environment was very conducive and supported Arabic language learning. This research can be used as a reference for institutions that want to manage a good learning environment. Further research can focus on other management functions, such as planning, organizing, and controlling.